The Theory of Money According to Imam Al-Ghazali - Chandra; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
Al-Ghazali in his works of Ihya Ulumuddin, al-Mustashfa Mizan, al-Amal and At-Tibr al-Masbuk fi al-Nasihah al-Mulk. In his works, Al-Ghazali explains many aspects of Islamic economics, especially Al-Ghazali's thoughts on the concept of money. This research aims to find out Imam Abu Hamid al-Ghazali's thoughts on the concept of money.  Al-Ghazali's thinking about the concept of money is inspired by the number of economic problems that occur in the barter system or exchange of goods. Al-Ghazali has explained several functions that money has, including as qiwam of al-dunya (unit of calculation), hakim mutawasith (measure of the value of goods), and al-mu'awwidlah (medium of exchange).